2002
DOI: 10.1177/088840640202500204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Instruction in Distance Learning Classes

Abstract: Techuology-mediated distance education (e.g., two-way interactive television, Web based instruction) is revolutionizing the delivery of university-level courses. The great promise provided by increased enrollments in efforts to meet supply and demand needs has made learning at a distance particularly popular in special education. In this research, student ratings were compared in a methods course that was affered on campus and off campus using different means of instruction. Students' ratings were also compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Beattie, Spooner, Jordan, Algozzine, and Spooner (2002) found that preservice teachers' course evaluations of a methods course in learning disabilities were similar whether presented in online or face-to-face formats. In addition to measuring preservice teachers' perceptions about distance education, several research teams (Caywood & Duckett, 2003;Pindiprolou, Peck Peterson, Rule, & Lignugaris-Kraft, 2003;Smith, Smith, & Boone, 2000) have investigated knowledge acquisition and application outcomes.…”
Section: Distance Educationmentioning
confidence: 98%
“…Beattie, Spooner, Jordan, Algozzine, and Spooner (2002) found that preservice teachers' course evaluations of a methods course in learning disabilities were similar whether presented in online or face-to-face formats. In addition to measuring preservice teachers' perceptions about distance education, several research teams (Caywood & Duckett, 2003;Pindiprolou, Peck Peterson, Rule, & Lignugaris-Kraft, 2003;Smith, Smith, & Boone, 2000) have investigated knowledge acquisition and application outcomes.…”
Section: Distance Educationmentioning
confidence: 98%
“…These systems have received considerable attention because they enhance interactivity and connectedness (Perraton, 2010). As a result, teacher education programs have begun embracing various web-based distance learning models to allow teachers to pursue additional education and professional growth experiences (Frey, 2008;Aldridge, Fraser, & Ntuli, 2009;Ludlow & Brannan, 1999;Beattie, Spooner, Jordan, Algozzine, & Spooner, 2002). These models have provided new instructional tools, such as asynchronous web support through emails or discussion lists and forums and synchronous teleconferencing or videoconferencing, especially in circumstances where students have a greater need for guidance and supervision.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies compared outcomes in traditional face-toface instructional formats versus courses that were taught using online components. Beattie, Spooner, Jordan, Algozzine, and Spooner (2002) found that preservice teachers' course evaluations of a methods course in learning disabilities were similar whether presented in online or face-to-face formats. In addition to measuring preservice teachers' perceptions about distance education, several research teams (Caywood & Duckett, 2003;Pindiprolou, Peck Peterson, Rule, & Lignugaris-Kraft, 2003;Smith, Smith, & Boone, 2000) have investigated knowledge acquisition and application outcomes.…”
Section: Distance Educationmentioning
confidence: 96%